Breeding and Selection of Grasses for Improved Drought Response: A Review - Johnson, Douglas A; Asay, Kay H (Annals of Arid Zone, 2016)
Water limits the establishment, growth and production of grasses on semi-arid rangelands, and plant improvement programs for these areas must be capable of screening breeding lines for response to drought. Although many techniques to evaluate various morphological and physiological characteristics have been proposed, few have been successfully used in plant breeding programs. Consequently, a need exists to identify and develop rapid, reliable screening techniques that can assess integrated plant response to drought in large plant populations. Improved seedling emergence has been achieved in Russian wildrye (psathyrostachys juncea (Fischer) Nevski] by selecting for emergence from deep seeding depth and long coleoptiles. Water uptake by roots is critical and screening for advanced seedling root growth in grasses offers considerable promise. In spite of the important role that stomatal control has in regulating plant water loss; limited success has been achieved in incorporating desirable stomatal characteristics into improved grass cultivars. Although osmotic adjustment appears beneficial in some crop species, more research is needed before grasses could be selected based on osmotic adjustment. Selection for improved water-use efficiency in cool-season grasses based on carbon isotope discrimination is a promising approach. Successful incorporation of these traits into improved grass cultivars necessitates close cooperation between breeders and physiologists.